Mensuração da energia despendida no jejum e no aporte calórico (MEL) em parturientes - Melo, Célia Regina Maganha E (2007)
This research aims to measure the energy spending in parturient women of low gestation risk. Participants were selected randomly and submitted to fasting (n=15; Group I) or honey ingestion (n = 15; Group II). Data were collected by means of capillary blood values and heart frequency monitoring. The paired t-test with a 5% significance level and Tukey's method were used in statistical analysis. The results showed that honey ingestion did not promote an overload in the mother's glucose; the lactate response demonstrated that the substrate offered was well used; the cardiorespiratory rate demonstrated good performance for both groups; the total energy spent during labor demonstrated that carbohydrate ingestion exerts significant influence, improving maternal anaerobic performance; the group which remained in fasting presented, immediately after labor, higher levels of lactate, showing the organism's efforts to compensate for the energy spent.